Inovasi Pengelolaan Lembaga Pendidikan bagi Kepala Sekolah Pasca Pandemi di Dinas Pendidikan Kabupaten Probolinggo - Syunu Trihantoyo; Supriyanto; M. Syahidul Haq; Shelly Andari (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2023)
The COVID-19 pandemic that occurred is like a succession that forms a new order. All areas of life have been significantly impacted by the pandemic, including education. Many countries, including Indonesia, have taken policies by closing schools to curb the spread of the virus. The closure of educational institutions then boils down to the policy of learning from home, teaching from home, or working from home online. In this case, this adjustment occurs in the managerial and learning fields. This problem will be resolved by the PKM team, with the principal being a member of the principal's working meeting.